Use of the costs of environmental quality and its impact on income (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Accompanied Activity Economic Unity some negative effects in the environment of air, water and soil pollution of difficult to measure each other for being the external costs and to be avoided such expenditures should be measured or estimated value to be disclosed environmental costs at the heart of the financial statements of economic unity to inform managers and users of the financial statements on the implications costs environmental .and impact in reducing environmental costs and increase future income and economic unit, was based on research into the inductive approach through books, letters, journals and the internet to cover the theoretical framework of the research. And to the analytical method deductive depending on the data and information available in one specialized in crude oil refining companies, a Midland Refineries Company (a public company), and the use of environmental and social internal and external quality costs through several measures and tools can measure the real environmental activities and disclosed, and develop appropriate measures to limit of them, and in line with the commensurate and consistent with the demands of stakeholders